A New Approach to Fault Detection in the Power Converter in Wind Turbine Conversion Systems - Abada Zhour; Ghoudelbourk Sihem; DIB Djalel (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
The detection of faults in a wind turbine chain is of prime importance in order to maintain safety, enhance reliability and improve economic performance. In addition, wind systems have to ensure a continuity of service for a considerable period of time in the event of an electrical fault in the network or a fault in one of the elements of the electromechanical conversion system. This paper presents a fault detection methodology of the power converter within a wind turbine chain, equipped with a Doubly-Fed Induction Generator (DFIG). A configurable, fast, and accurate scheme is developed, the basis of which is the reliable identification of the failed switch. The solution proposed in this work involves the deployment of a redundant arm in the event of a fault; the replacement arm is utilized while waiting for a maintenance or repair operation to be carried out. The approach developed in this paper provides continuity of service after the occurrence of a fault in the network system and fault detection time is reduced. The validity of the proposed identification methodology is assessed by means of simulation of the model of a wind turbine conversion system.